2003
DOI: 10.1002/jnr.10696
|View full text |Cite
|
Sign up to set email alerts
|

Complementary DNA cloning and characterization of RANDAM‐2, a type I membrane molecule specifically expressed on glutamatergic neuronal cells in the mouse cerebrum

Abstract: A membrane-surface glycoprotein, RANDAM-2, is one of the neuronal cell lineage-specific antigens involved in the neuronal differentiation of P19 embryonic carcinoma (EC) cells and the mouse central nervous system (CNS). Complementary DNA cloning of RANDAM-2 indicated that its nucleotide sequence completely matched that of PA2.26 antigen, a sialomucin-like transmembrane glycoprotein previously found on tumorigenic keratinocytes. RANDAM-2 transcripts were detectable from the embryonic stage of 6.5 days, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…The marked enhancement of ppGalNAc-T13 expression was reminiscent of a typical mucin-type O-glycoprotein PDPN, which has also been reported to increase dramatically during the neuronal differentiation of P19 cells (33,34). Consistently, such an increase was also observed in our neuronal differentiation model of both primary cortical neural precursor cells and P19 cells by Western blotting analysis (Fig.…”
Section: The Regulatory Effects Of Ppgalnac-t13 On Neuronal Differentsupporting
confidence: 87%
“…The marked enhancement of ppGalNAc-T13 expression was reminiscent of a typical mucin-type O-glycoprotein PDPN, which has also been reported to increase dramatically during the neuronal differentiation of P19 cells (33,34). Consistently, such an increase was also observed in our neuronal differentiation model of both primary cortical neural precursor cells and P19 cells by Western blotting analysis (Fig.…”
Section: The Regulatory Effects Of Ppgalnac-t13 On Neuronal Differentsupporting
confidence: 87%
“…There are numerous reports on the expression of podoplanin in tumors (see section 2.7.1). Kotani et al (2003) have studied podoplanin during mouse neurogenesis, finding positive cells from day E6.5 and in adult brain in glutamatergic (but not GABAergic) neurons. Other reports describe podoplanin expression in other tissues: , podoplanin has been found in the choroid plexus by Williams et al (1996) and Scholl et al (1999); Song et al (2014) reported its presence in cortical neurons and its up-regulation during inflammation; it has been also described in cells of the ciliary epithelium of the eye (Williams et al, 1996); Sonne et al (2006) have identified podoplanin with the oncofoetal antigen M2A, which is expressed in developing testis and in carcinoma in situ.…”
Section: Tissue Distributionmentioning
confidence: 99%
“…Other homologues include the canine receptor for the influenza C virus gp40 (Gandarillas et al, 1997) and its human homologue gp36 (Zimmer et al, 1999) and RANDAM-2 (Kotani et al, 2003), the membrane glycoprotein expressed in neuronal cells during mouse neurogenesis. Podoplanin is used as a specific marker for lymphatic endothelium in histopathology (Breiteneder-Geleff et al, 1999).…”
Section: Introductionmentioning
confidence: 99%